2019
DOI: 10.1111/itor.12726
|View full text |Cite
|
Sign up to set email alerts
|

Conditional value‐at‐risk beyond finance: a survey

Abstract: A large number of problems involve making decisions in an uncertain environment and, hence, with unknown outcomes. Optimization models aimed at controlling the trade‐off between risk and return in finance have been widely studied since the seminal work by Markowitz in 1952. In financial applications, shortfall or quantile risk measures are receiving ever‐increasing attention. Conditional value‐at‐risk (CVaR) is arguably the most popular of such measures. In the last decades, optimization models aimed at contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 156 publications
0
19
0
1
Order By: Relevance
“…An overview of applications where CVaR have been used can be found in Ref. [75].…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…An overview of applications where CVaR have been used can be found in Ref. [75].…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…CVaR η measures the average profit falling below the η‐quantile level VaR η (Chen et al., 2017b; Li et al., 2018; Zhou et al., 2018b). That is, CVaR η is sensitive to worst outcomes (Filippi et al., 2020). When a manufacturer is risk averse, the manufacturer's decisions and the profit will be influenced by his risk behavior.…”
Section: Extension: the Risk‐averse Scenariomentioning
confidence: 99%
“…The concept of CVaR has gained much attention since Rockafellar and Uryasev [57] showed that it can be formulated using a linear model. Apart from in radiation therapy, CVaR has been used in a wide range of applications, see [58] for a review. To focus on its use in radiation therapy, we refer to it as mean-tail-dose (MTD).…”
Section: Mean-tail-dose Modelsmentioning
confidence: 99%